The Elliniko Airport: Contested Politics and the Production of Urban Space in Athens, 1938-2014 - (:unkn) unknown (My University, 2014)
This study traces the historical forces that conditioned the dearth of public spaces in Athens, Greece, and through the case study of the city's first civil airport, examines the current redevelopment plans of Athens' largest remaining open space as part of a wider process of urban transformation. After serving the city for sixty years, the airport closed its doors in 2001, and since then the site has remained vacant. The government aims at attracting investments in upscale tourism and real estate, hoping to reposition this sector of the city as a thriving business center and entertainment destination. Yet, given the severe environmental and social problems of Athens, the implementation of an urban development agenda which promotes the further commercialization of urban space will make a livable city--so dependent on open public space--a more difficult and unlikely contingency. It is precisely this possibility that unites a diverse group of community actors that contest the government's plans arguing instead for the creation of a metropolitan park, and presenting this site as a space of insurgent citizenship. The redevelopment process of the Elliniko airport is a central node in understanding the symbolic construction of Athens' restructuring as a competitive city, while on the other hand, it figures as a paradigmatic case in the analysis of conflicts between economic development and sustainability.
Keywords: Airport Redevelopment; Economic Crisis; Greece; Neoliberalism; Privatization; Urban Politics